2011
DOI: 10.4236/jmp.2011.210139
|View full text |Cite
|
Sign up to set email alerts
|

Materials for Spintronics: Magnetic and Transport Properties of Ultrathin (Monolayer Graphene)/MnO(001) and MnO(001) Films

Abstract: Results of investigations of band structure, Fermi surface and effective masses of charge carriers in the ultrathin (monolayer graphene)/MnO(001) and MnO(001) films are presented using the method of the density functional theory. Features of spin states of valence band and Fermi level as well as an interatomic interaction in these systems are discussed. A magnetic moment at Mn atom is estimated and an effect of spin polarization at atoms of oxygen and carbon has been revealed which natures are discussed. By ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 62 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…For example, based on transport measurements, Wang et al [2015] concluded that graphene on yttrium-iron garnet becomes magnetic, without being able to determine or even estimate the moment. The induced magnetism in graphene on magnetic insulators such as MnO and EuO substrates was investigated using density-functional theory calculations and spin-polarization was inferred in graphene in both the substrates [IIyasov 2011, Yang 2013. Similar studies on graphene on Fe2O3 indicate a significant charge transfer from graphene to surface of Fe2O3, which results in a significant shift of the Fermi energy away from the Dirac point.…”
mentioning
confidence: 91%
“…For example, based on transport measurements, Wang et al [2015] concluded that graphene on yttrium-iron garnet becomes magnetic, without being able to determine or even estimate the moment. The induced magnetism in graphene on magnetic insulators such as MnO and EuO substrates was investigated using density-functional theory calculations and spin-polarization was inferred in graphene in both the substrates [IIyasov 2011, Yang 2013. Similar studies on graphene on Fe2O3 indicate a significant charge transfer from graphene to surface of Fe2O3, which results in a significant shift of the Fermi energy away from the Dirac point.…”
mentioning
confidence: 91%
“…[40][41][42][43] What cannot be ignored is that remarkable breakthrough has also been achieved in 2D materials synthesis and MTJs begin to be created based on them. 44 Due to its low dimensionality and quantum nature, the use of 2D materials adds many unique features into MTJs such as flexibility, and extremely high scaling. 45,46 First-principles calculations based on density functional theory (DFT) have been the most widely used method in theoretical studies of 2D materials and their applications in devices such as MTJs.…”
Section: Introductionmentioning
confidence: 99%
“…Growth of the metal oxide film on graphene layer and other metal's surfaces is an important synthesis methods of hybrid materials for different applications such as catalysis, electrochemical devices, and biomedical materials. [1], [2] Manganese oxides and oxyhydroxides are of considerable interest in many technological applications, for example, electrochemical reaction, batteries, catalysis and magnetic materials due to their outstanding structural diversity combined with novel chemical and physical properties. [3], [4] A clear understanding of the crystallization pathway of manages oxide film controlled by graphene bilayers is essential for the synthesis of such hybrid materials.…”
mentioning
confidence: 99%